2004
DOI: 10.1002/jtra.10053
|View full text |Cite
|
Sign up to set email alerts
|

Can long‐term exposure to chromium improve insulin sensitivity in chromium mine workers?

Abstract: The purpose of this work was to evaluate insulin sensitivity in chromium mine workers exposed to chromium chronically. Body mass index, waist circumference, fat mass and percent, lipid levels, serum glucose, insulin, leptin and chromium levels, HOMA (%S), and HOMA (%B) values were measured in 93 male workers and 94 age-and body mass index-matched healthy controls. Fat mass and fat percent of workers were higher than control subjects (P < 0.01 and P < 0.0001, respectively). Mean insulin level of the workers was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The lack of Cr deficiency or some other etiological factors may provide an explanation. A number of human studies (Anderson, 2000;Tuzcu et al, 2004), studies on pigs (Wenk et al, 1995), horses (Pagan et al, 1995;Ott and Kivipelto, 1999), cattle and rats (Kim et al, 2004) have confirmed the possibility of influencing glucose tolerance and insulin resistance by Cr supplementation.…”
Section: Metabolism Of Carbohydratesmentioning
confidence: 99%
“…The lack of Cr deficiency or some other etiological factors may provide an explanation. A number of human studies (Anderson, 2000;Tuzcu et al, 2004), studies on pigs (Wenk et al, 1995), horses (Pagan et al, 1995;Ott and Kivipelto, 1999), cattle and rats (Kim et al, 2004) have confirmed the possibility of influencing glucose tolerance and insulin resistance by Cr supplementation.…”
Section: Metabolism Of Carbohydratesmentioning
confidence: 99%
“…38 Daily mean intake for chromium has been reported to be around approximately 33 μg. 39 Previous studies have suggested the possibility of chromium supplementation in influencing glucose tolerance and insulin resistance in humans, 40,41 and rats. 42 In vitro experiments showed that chromium and insulin supplementation to animal tissues resulted in increased glucose oxidation to carbon dioxide and water, increased glycogenesis and conversion of glucose to lipids, as well as increased glucose utilization.…”
Section: Resultsmentioning
confidence: 99%
“…When glucose metabolism was assessed in workers employed in this occupational setting, Cr exposure seemed to exert significant beneficial effects improving glucose tolerance with respect to unexposed controls (Wrobel et al, 1999), particularly in the older, even more obese worker subgroups (Stupar et al, 1999). Comparably, significant Cr beneficial effects on insulin sensitivity, cell function and insulin levels were reported by Tuzcu et al (2004) in mine workers exposed to the metal compared to controls. The authors suggested that this may be due to a Crinduced lower fat mass or to an increase in the number and activation of insulin receptors (Davis and Vincent, 1997;Morris, 1999).…”
Section: Metals and Dmmentioning
confidence: 98%